Western Wall Plaza Excavations. - Weksler-Bdolah, Shlomit (Israel Antiquities Authority, 2021)
This volume is the third in a series describing the results of salvage excavations conducted in the northwestern part of the Western Wall Plaza. This third volume presents the small finds of the Early Roman to Byzantine periods, most of which originated in the 'Roman refuse dump', a fill deposited into an abandoned quarry during infrastructure work, and then sealed by the paving stones of the Eastern Cardo. The well-preserved and securely dated finds (70-130 CE) can be clearly attributed to the Roman army. The volume describes the numerous quarries at the site that shaped the surface topograph.